POLICE STRESS FACTORS AMONG LAW ENFORCEMENT AGENCIES: A COMPARISON STUDY OF US AND TURKISH POLICE - Hakan Batırhan Kara; Ercan Sunger; Alican Kapti (European Scientific Journal, ESJ, 2015)
Policing is one of the most stressful jobs in the world. However, the factors which cause stress (stressors) can be different among the police officers in different countries. This paper focuses on the differences about the police occupational stressors between Turkish National Police (TNP) and the United States Law Enforcement Agencies. Turkey is a developing country bordering between Asia and Europe. Not only does its geographical condition cause some international policy problems, but also it causes a lot of policing problems: Such as being a bridge for drug and gun smugglers, being a bridge for human trafficking, and being a target for terrorist organizations. On the other side, the United States of America is a developed country and also known as the superpower of the world. This study tries to answer the question of “Are there any differences between a developed country’s police force and a developing country’s police force in terms of existing stress factors?”